Franklin in Siberia? - Lieutenant Bedford Pim's Proposal to Search the Arctic Coast of Siberia, 1851-52 - Barr, William (ARCTIC, 1992)
Like many of his contemporaries, Lieutenant Bedford Pim, of the Royal Navy, believed in the existence of an "open polar sea" beyond a zone of coastal ice around the margins of the Arctic Ocean. On the basis of this, in fall 1951 he postulated that Sir John Franklin's expedition had sailed north through Wellington Channel and then set a course across the "Polar Sea" directly for Bering Strait, but had then become entangled in an ice-bound chain of islands extending from what are now the Canadian Arctic Islands to the vicinity of Ostrov Vrangel'ya. Having been refused Admiralty approval for his plan to mount a small overland expedition to Chukotka, from whence he proposed to push north across the sea ice in search of Franklin's ships, Pim was able to gain the support of Lady Franklin and the Royal Geographical Society. He travelled to St. Petersburg in December 1851 but after considerable delay was refused permission by the Russian authorities to proceed farther east. The main stated reason for this refusal was that the Russians had somehow translated Pim's plans for a small expedition of two or three men into an operation that would necessitate 1200-1500 sledge dogs; it was anticipated that such an operation would seriously disrupt the economy of the Kolyna basin and cause real hardship to the local people. One can only speculate as to the reasons for the lack of Russian cooperation; one suspects, on the basis of Pim's own account, that the tone of his remarks to the tsar during a personal audience and the implied lack of confidence in the tsar's commitment to arrange for a search to be mounted along the arctic coasts of Siberia for wreckage or survivors from the Franklin expedition may have contributed significantly to the rejection of his proposal.Key words: Franklin search, Siberia, Lieutenant Bedford RÉSUMÉ. Comme bien de ses contemporains, le lieutenant BedfordP im de la Royal Navy, croyait B l’existence d’une mer polaire ouverte, au-delà d’une zone de glace côtière bordant l’océan Arctique. Fort de cette ...